Structural integration of personality mediates the effects of adverse and protective childhood experiences on the course of psychotherapy [script] - Kindermann, David; Dönnhoff, Ivo; Orth, Maximilian; Friederich, Hans-Christoph; Nikendei, Christoph (Universität, 2023)
Analysis of the psychotherapy data from the HIP (Heidelberger Institute for Psychotherapy). We checked whether the speed of patients' symptom impro...